Effect of four kinds of natural antimicrobial compounds on the biofilm formation ability of Listeria monocytogenes isolated from beef processing plants in China. (November 2020) - Liu, Yunge; Dong, Pengcheng; Zhu, Lixian; Zhang, Yimin; Luo, Xin
Abstract: The objective of this study was to evaluate the inhibitory effect of four natural antimicrobial compounds on the biofilm formation of Listeria monocytogenes ( L. monocytogenes ) isolated from beef processing plants in China. Firstly, biofilm-forming ability of the isolated L. monocytogenes (n = 131) was investigated. Furthermore, the biofilm inhibitory assay of four natural antimicrobial compounds (cinnamaldehyde, eugenol, resveratrol and thymoquinone) was tested at subminimum inhibitory concentrations (sub-MICs), with sodium hypochlorite as a control. The results showed that all 131 tested strains produced biofilms, and 67.2% (n = 88) were strong biofilm producers. The strongest biofilm formation capacity occurred at 25 °C and pH 7.4, and the biofilm-forming ability of L. monocytogenes is specific at the genotype level. Four natural antimicrobial compounds were effective at inhibiting biofilm formation of L. monocytogenes at sub-MIC (1/4 × MIC and 1/8 × MIC), and the effective inhibitory concentrations of resveratrol and thymoquinone were as low as 25 μg/mL and 6.25 μg/mL. Scanning electron microscopy (SEM) showed distinguishable inhibitory effect of natural antimicrobial compounds on biofilm formation. These findings indicate a potential application of natural antimicrobial compounds in the prevention of L. monocytogenes biofilm. Highlights: Among 131 strains isolated from beef abattoir, 67.2% were strong biofilm producers. The strongest biofilm formation capacity occurred at 25 °C and pH 7.4. Four natural compounds all had effectively anti-biofilm activity at sub-MIC. SEM showed obvious inhibitory effect of natural compounds on biofilm formation. Resveratrol and thymoquinone are potential anti-biofilm agents of L. monocytogenes.